ANALISIS MAKNA TRADISI ACCERA KALOMPOANG DALAM KEBUDAYAAN KESULTANAN GOWA - Dewi Larasati, Dinda; Sophia Sihotang, Bella; Christhy Sihotang, Ellen; Azazeera, Jihan; Fauzi Damanik, Muhammad; Suhendro Lukitoyo, Pristi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Accera Kalompoang tradition is a traditional ritual that holds a significant place in the cultural system and is a symbol of power during the Gowa Sultanate in Gowa. This ritual involves the purification of royal heirlooms, performed periodically as a form of respect for ancestral heritage and as a symbol of the historical legitimacy of royal power. This study aims to analyze the symbolic meaning, cultural values, and social functions of the Accera Kalompoang tradition in the context of preserving the cultural identity of the Gowa people. This research employed qualitative methods with a descriptive-analytical approach through a literature review of various relevant historical, anthropological, and cultural studies sources. The results indicate that the Accera Kalompoang tradition functions not only as a traditional ritual practice but also represents symbolic constructions related to the legitimacy of power, respect for ancestors, and a mechanism for preserving the community's collective memory. In the contemporary context, this tradition also serves as a medium for preserving cultural heritage, strengthening the cultural identity of the Gowa people amidst the dynamics of social change. Thus, Accera Kalompoang can be understood as a cultural practice with historical, symbolic, and social dimensions in maintaining the continuity of the traditions of the Gowa Sultanate.